1998
DOI: 10.1177/019262339802600208
|View full text |Cite
|
Sign up to set email alerts
|

Receptor and Nonreceptor-Mediated Organ-Specific Toxicity of Di(2-ethylhexyl)phthalate (DEHP) in Peroxisome Proliferator-Activated Receptorα-Null Mice

Abstract: The peroxisome proliferator-activated reccptora (PPARa) is the mediator of the biological effects of pcroxisome proliferators through control of gene transcription. To determine if the toxic effects of di(2-ethylhexy1)phthalate (DEHP) are mediated by PPARa, we examined its effect in PPARa-null micc. Male Sv1129 mice. PPARa-null (-/-) or wild-typc (+I+) were fed nd libirirrn either a control diet or one containing 12.000 ppm DEHP for up to 24 wk. Significant body weight loss and high mortality was observcd in (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
154
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(166 citation statements)
references
References 19 publications
10
154
2
Order By: Relevance
“…DEHP-induced glomerulonephritis was found for the first time in this study. The known DEHP tubulointerstitial toxicities, reported in previous studies using high dosages of DEHP in short-term periods (14,22), did not appear in our study. The discrepancy in renal pathology between the earlier studies and this study probably is derived from differences in study design.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…DEHP-induced glomerulonephritis was found for the first time in this study. The known DEHP tubulointerstitial toxicities, reported in previous studies using high dosages of DEHP in short-term periods (14,22), did not appear in our study. The discrepancy in renal pathology between the earlier studies and this study probably is derived from differences in study design.…”
Section: Discussioncontrasting
confidence: 79%
“…These tubulointerstitial lesions were localized around the sclerotic glomerular lesions (Figure 3). The lesions, reported in earlier studies, such as cystic tubular dilation, tubular necrosis, tubular pigmentation, and papillary mineralization (14,22), were scarcely detected here. These findings suggest that secondary tubulointerstitial lesions developed after glomerular damages occurred.…”
Section: Dehp Induces Immune-complex Glomerulonephritiscontrasting
confidence: 72%
See 1 more Smart Citation
“…The relatively recent development of PPARa gene knockout mice has now confirmed that the PPARa receptor is responsible for mediating the effects induced by the peroxisome proliferator-inducing agents clofibrate, WY-14,643 and DEHP (i.e., hepatomegaly, increases in peroxisomes and enzyme induction) (Lee et al 1995;Ward et al 1998). It is also responsible for the transient increase in cell proliferation commonly observed immediately after treatment as well as the more variable low level sustained increases in proliferation occasionally observed following chronic treatment (Cattley 2004).…”
Section: The Role Of the Ppara Receptormentioning
confidence: 99%
“…In parallel, interaction of some phthalate metabolites with PPARa are responsible for in vivo effects, such as malformations in the male reproductive tract and liver cancer in mice and rats. 40,49,50 Amazingly, fairly little is known on the metabolic consequences of phthalate exposure. Therefore, we addressed the issue of interference of EDCs with PPARregulated processes using the MEHP metabolite of the DEHP plasticizer as a model.…”
Section: Pparc and Phthalates: Stepping In With The Definition Of A Smentioning
confidence: 99%